2019
DOI: 10.1002/jcp.28357
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin supplementation during in vitro maturation of oocyte enhances subsequent development of bovine cloned embryos

Abstract: Oocyte quality, which is directly related to reprogramming competence, is a major important limiting factor in animal cloning efficiency. Compared with oocytes matured in vivo, in vitro matured oocytes exhibit lower oocyte quality and reprogramming competence primarily because of their higher levels of reactive oxygen species. In this study, we investigate whether supplementing the oocyte maturation medium with melatonin, a free radical scavenger, could improve oocyte quality and reprogramming competence. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 54 publications
3
57
0
1
Order By: Relevance
“…Because melatonin reduces ROS and oxidative stress via its direct antioxidative functions, it improves cellular integrity ( Figure 3). However, indirect effects of melatonin via membrane receptors (MT1, MT2) and/or nuclear receptors (RORα) are also important to understand the processes by which melatonin alters the level of oxidative stress [56,57]. Figure 3 summarizes the mechanism of melatonin that are assumed to improve oocyte maturation and quality based on reports to date.…”
Section: Oocyte Maturation Embryo Development and Melatoninmentioning
confidence: 99%
“…Because melatonin reduces ROS and oxidative stress via its direct antioxidative functions, it improves cellular integrity ( Figure 3). However, indirect effects of melatonin via membrane receptors (MT1, MT2) and/or nuclear receptors (RORα) are also important to understand the processes by which melatonin alters the level of oxidative stress [56,57]. Figure 3 summarizes the mechanism of melatonin that are assumed to improve oocyte maturation and quality based on reports to date.…”
Section: Oocyte Maturation Embryo Development and Melatoninmentioning
confidence: 99%
“…Up to now, electrofusion was the most commonly used method for most SCNT studies 8,9,18,19 . Regarding the piezo microinjection method, researchers were concerned about the risk of mercury contamination during the injection using micropipettes 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin is an antioxidant and free-radical scavenger that may be beneficial for the production of developmentally competent embryos when electrofusion is employed 5 . Melatonin effectively reduced oxidative stress and improves the development and hatchability rates of preimplantation fertilized embryos and SCNT embryos in cows, pigs, goats, mice and other species 5,18,28,29 . The results in the present study showed that greater electrical stimulation induced higher ROS level in SCNT embryos, which were reduced by incubation with melatonin.…”
Section: Figure 1 Effects Of Electrofusion On Rabbit Scnt Embryos (A)mentioning
confidence: 99%
“…The purity of isolated cortical stromal cells and theca cells was evaluated using previously described methods with minor modifications (An et al, ; Qiu et al, ; Wang et al, ). Briefly, cortical stromal cells and theca cells were fixed with Immunol Staining Fix Solution (Beyotime Institute of Biotechnology) for 20 min and then were permeabilized with 0.2% Triton X‐100 for 15 min.…”
Section: Methodsmentioning
confidence: 99%